DESIGNING THE SYLLABUS OF ENGLISH FOR TOURISM SUBJECT BASED ON THE INDONESIAN QUALIFICATION FRAMEWORK - Ashari P Swondo (Journal MELT (Medium for English Language Teaching), 2018)
The increasing development of the tourism industry in Indonesia, especially in North Sumatera has an impact on the growing need for qualified human resources in the field of tourism. Someone who works in the field of tourism businesses is required to have competence in English to be able to communicate with guests both orally and literally in accordance with the level of qualifications. Therefore, the syllabus used in the teaching and learning of English in the field of tourism must be designed for the achievement of competence which is based on the Indonesian Qualification Framework Standard. The purposes of this paper are to present a theoretical discussion on the teaching and learning of English in the field of Tourism and the second is to provide a proposed syllabus which can be used as a reference in the implementation of the training, curriculum development and the preparation of modules in producing and developing the human resources that are competent and professional in the field of tourism.